Educational Value and Assessment of Short Surgical Cases in Outpatient Settings, A Systematic Review of Resident Learning Outcomes and Training Gaps - Ul Haq, Atta; Imran, Muhammad; Rashid, Yasar; Arshad Khan, Muhammad; Sarfaraz, Junaid; Ahmad, Arbab Farooq (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVE: To assess the impact of short outpatient surgical cases on residents' procedural confidence, clinical reasoning, communication, and professional development. METHODOLOGY: We systematically searched PubMed, Scopus, Web of Science, and ERIC through July 2025 following PRISMA 2020. We included studies reporting educational outcomes for surgical residents. The quality assessment was made via CASP, Newcastle–Oawa, and JADAD tools. Mixed-methods synthesis was performed; quantitative data were pooled where possible. RESULTS: Twelve studies (6 qualitative/mixed-methods, 4 observational, 2 intervention) reported that outpatient experience enhanced procedural confidence, clinical reasoning, communication, and teamwork. Meta-analysis demonstrated a significant increase in self-reported confidence, with an SMD of 0.55; 95% CI 0.30–0.80. Major barriers to effective learning included high workload and limited supervision. CONCLUSION: Brief outpatient surgical cases have been shown to possess valuable educational merit and contribute to resident competency development. Structured outpatient exposure is advisable.